Spotkania intertekstualne. O dialogu Hélène Cixous z Jacques’em Derridą - Kopka, Aleksander (Wydawnictwo Naukowe UAM, 2014)
Where else, if not “in a text”, can two bright minds, or two writers, meet? Is it possible for two intellectuals who engage in a dialogue to understand each other without appropriation, i.e. without constantly borrowing from each other and commenting on each other’s ideas? This essay is an attempt at answering these questions by using the unique relation between Hélène Cixous and Jacques Derrida as an example. The friendship between these two is based on efforts to understand each other’s thoughts and writings – but all this is not without respect for each other’s singularity, sovereignty and intimacy.
Intertextual meetings: a dialogue between Hélène Cixous and Jacques Derrida